CEO power, government monitoring, and bank dividends - Onali, Enrico; Galiakhmetova, Ramilya; Molyneux, Philip; Torluccio, Giuseppe (Elsevier, 2016)
We investigate the role of CEO power and government monitoring on bank dividend policy for a sample of 109 European listed banks for the period 2005–2013. We employ three main proxies for CEO power: CEO ownership, CEO tenure, and unforced CEO turnover. We show that CEO power has a negative impact on dividend payout ratios and on performance, suggesting that entrenched CEOs do not have the incentive to increase payout ratios to discourage monitoring from minority shareholders. Stronger internal monitoring by board of directors, as proxied by larger ownership stakes of the board members, increases performance but decreases payout ratios. These findings are contrary to those from the entrenchment literature for non-financial firms. Government ownership and the presence of a government official on the board of directors of the bank, also reduces payout ratios, in line with the view that government is incentivized to favor the interest of bank creditors before the interest of minority shareholders. These results show that government regulators are mainly concerned about bank safety and this allows powerful CEOs to distribute low payouts at the expense of minority shareholders.